Cross Ventilation in High-Rise Apartment Building: Effect of Ventilation Shaft Aperture Configuration on Air Velocity and Air Flow Distribution - Fahmi, M. Rizal; Defiana, Ima; Antaryama, I. Gusti Ngurah (IPTEK Journal of Proceedings Series, 2018)
Ventilation shaft can be used in apartment units to provide cross ventilation by creating a pressure difference between the room’s windward opening and outlet at the roof. The previous research about ventilation shaft has shown its potential in providing good natural ventilation in high-rise apartment building. This paper examines the influence of ventilation shaft aperture configuration on its ability to generate air movement and uniform flow distribution. The experiment is carried out using computational fluid dynamics with RNG k-e calculation method. Ventilation shaft system with a uniform aperture can produce very high air velocity only at the top floor while ventilation shaft system with internal aperture size increased from the upper floor to the lower floor can produce better air flow distribution